Partial replacement of soybean meal with soybean silage in lactating dairy cows diet: part 1, milk production, digestibility, and N balance. Issue 1 (31st December 2022) - Rota Graziosi, Andrea; Colombini, Stefania; Crovetto, Gianni Matteo; Galassi, Gianluca; Chiaravalli, Maria; Battelli, Marco; Reginelli, Davide; Petrera, Francesca; Rapetti, Luca
Abstract: The high reliance of the European livestock sector on imported soybean meal (SBM), especially from South America, poses environmental problems, like greenhouse gas emissions for transportation and land-use change with the loss of carbon stock and biodiversity. Aim of the present study was to evaluate the partial substitution of SBM with whole-plant soybean silage in the diet of dairy cows. Thirty-six lactating Holstein cows were arranged according to a change-over design, with 2 weeks of adaptation and 5 days of sampling per period. A control diet (CON) was based on maize silage and SBM, representing 10.7% of total dry matter (DM). In a soybean silage diet (SBS) 35% (on DM basis) of SBM was replaced by soybean silage. The dietary treatment did not affect DM intake, milk production, and dairy efficiency while cows fed SBS resulted in lower milk crude protein (3.43 vs. 3.55%, p  < .001) and higher milk urea (30.5 vs. 28.7 mg/dL, p  = .002), in comparison with CON. Nutrients digestibility was lower for SBS than CON; particularly fibre digestibility was 31.5 vs. 38.8% ( p  < .001). The efficiency of nitrogen utilisation was higher for CON than SBS (32.7 vs. 31.3%, p  = .003). Soybean silage did not penalise feed intake and milk production. However, to fully exploit this forage, digestibility, and nitrogen utilisation efficiency should be improved. Highlights: Soybean silage can substitute one-third of soybean meal in dairy cow diet Soybean silage inclusion in the diet did not affect milk yield and DMI Soybean silage inclusion in the diet reduced N use efficiency